The Effect of Low-Density Polyethylene Plastics’s Thickness as a Packaging Materials on the Quality of Celery (Apium gravelens L.) during Cold Storage - Hadi, I Kadek Puja Harta; Pudja, Ida Ayu Rina Pratiwi; Arda, Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Using the right thickness of low-density polyethylene (LDPE) packaging can maintain the quality of celery and also can extend their storage time. The purpose of this study was to determine the effect of LDPE plastic thickness as a packaging material on the quality of celery during storage at low temperature and to determine which thickness level of LDPE plastic can maintain the best quality celery. Experimental research was used in this study. In this study, Completely Randomized Design (RAL) was used as experimental design. The thickness level that used for this study were 0.02 mm; 0.03 mm; 0.04 mm; 0.05 mm, 0.06 mm. Observations were made once every 3 days and each treatment was repeated 3 times at a storage temperature of 10 ± 20C for 18 days. The parameters in this study were weight loss, water content, color, texture, freshness, and the scent. The results of the analysis of variance showed that the thickness level of LDPE plastic as packaging material for celery had a very significant effect (P˂0.01) towards the research parameters. The best treatment was obtained from 0.04 mm size with a weight loss of 4.64%, 18.97 on color, a texture of 0.0455 N, a water content of 90.22%, a freshness level of 4.87 and the scent of 5.00. The conclusion that the thickness level at 0.04mm of LDPE plastic is the best solution to maintain quality of celery and reached 18 days of storage time